2013
DOI: 10.12809/hkmj133920
|View full text |Cite
|
Sign up to set email alerts
|

How can the R.E.N.A.L. nephrometry scoring system aid management of a solid renal mass?

Abstract: OBJECTIVES. To investigate use of the R.E.N.A.L. nephrometry score in relation to the choice of treatment and postoperative complications for renal masses. DESIGN. Case series. SETTING. A tertiary referral hospital in Hong Kong. PATIENTS. Data of patients undergoing nephrectomy were collected retrospectively from a clinical database and analysed. A R.E.N.A.L. nephrometry score was allocated to each renal tumour by a blinded qualified radiologist, utilising computerised imaging systems. Patient demographics, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…In our present study, from 52 patients that were treated with radical nephrectomy, 29 patients were categorized as high complexity tumor (100% of total) and 23 were categorized as moderate complexity tumor (80% in total), and none were categorized as low complexity tumor. This data correlates well with the study conducted by Canter et al [14] and Wong et al [6] which showed that patients treated with radical nephrectomy were of moderate and high complexity;…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In our present study, from 52 patients that were treated with radical nephrectomy, 29 patients were categorized as high complexity tumor (100% of total) and 23 were categorized as moderate complexity tumor (80% in total), and none were categorized as low complexity tumor. This data correlates well with the study conducted by Canter et al [14] and Wong et al [6] which showed that patients treated with radical nephrectomy were of moderate and high complexity;…”
Section: Resultssupporting
confidence: 92%
“…It was different from the radical nephrectomy group where there were no patients categorized as low complexity tumor. This profile correlates well with Canter et al [14] study and Wong et al [6] study. From both of those studies, it was shown that patients with low complexity tumor and some of the moderate complexity tumors were being treated with nephronsparing surgery/partial nephrectomy [6,14].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations